2014
DOI: 10.1371/journal.pone.0105326
|View full text |Cite
|
Sign up to set email alerts
|

The Differential Expression of EphB2 and EphB4 Receptor Kinases in Normal Bladder and in Transitional Cell Carcinoma of the Bladder

Abstract: Effective treatment of transitional cell carcinoma (TCC) of the bladder requires early diagnosis. Identifying novel molecular markers in TCC would guide the development of diagnostic and therapeutic targets. Ephrins mediate signals via tyrosine kinase activity that modulates diverse physiologic and developmental processes, and ephrins are increasingly implicated in carcinogenesis. The aim of our study was to examine the differential regulation of EphB4 and EphB2 in normal bladder and in TCC of the bladder in 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 31 publications
2
17
1
Order By: Relevance
“…Based on these findings, EphB2 expression was evaluated in total protein cell extracts, finding 3 times higher levels in MB49-I cells than in MB49 cells ( Figure 4G). These findings are in agreement with the association reported between high EphB2 expression and EMT induction and progression of human cervical cancer (69), although they contrast with a report describing its decrease in human BC samples (70).…”
Section: Expression Analysis Of Ephrin-b1 and Related Proteins In Mb4supporting
confidence: 92%
“…Based on these findings, EphB2 expression was evaluated in total protein cell extracts, finding 3 times higher levels in MB49-I cells than in MB49 cells ( Figure 4G). These findings are in agreement with the association reported between high EphB2 expression and EMT induction and progression of human cervical cancer (69), although they contrast with a report describing its decrease in human BC samples (70).…”
Section: Expression Analysis Of Ephrin-b1 and Related Proteins In Mb4supporting
confidence: 92%
“…In contrast, activation of EphB2 has been shown to promote invasion of glioblastoma in vivo (Wang et al, 2012). In transitional cell carcinoma of the bladder, loss of EphB2 and gain of EphB4 expression have been reported to be associated with the tumor progression, and EphB4 inhibitors have been shown to have antitumor properties in xenograft model of this tumor (Li et al, 2014). Previous studies on the role of Eph/ephrin signaling in the progression of skin cancer have identified members of EphA subfamily, especially EphA2, as tumor suppressor in epidermal keratinocytes (Guo et al, 2006b).…”
Section: Discussionmentioning
confidence: 99%
“…Both EphB4 and its sole physiologically relevant ligand, ephrin B2 (EFNB2), are membrane bound, and their interaction initiates forward signaling through EphB4 and reverse signaling through EFNB2 1 . EphB4 is overexpressed in many solid tumors, including those of the ovary 2,3 , breast 4,5 , colon 6 , prostate 7,8 , and bladder 9 . High EphB4 expression is associated with shorter disease-free survival in patients with epithelial ovarian cancer 3,10 .…”
mentioning
confidence: 99%